Advanced Development of Sustainable PECVD Semitransparent Photovoltaics: A Review - Kabongo, G. L.; Mothudi, B. M.; Dhlamini, M. S. (Frontiers in Materials, 2021)
Energy is the driving force behind the upcoming industrial revolution, characterized by connected devices and objects that will be perpetually supplied with energy. Moreover, the global massive energy consumption increase requires appropriate measures, such as the development of novel and improved renewable energy technologies for connecting remote areas to the grid. Considering the current prominent market share of unsustainable energy generation sources, inexhaustible and clean solar energy resources offer tremendous opportunities that, if optimally exploited, might considerably help to lessen the ever-growing pressure experienced on the grid nowadays. The R&D drive to develop and produce socio-economically viable solar cell technologies is currently realigning itself to manufacture advanced thin films deposition techniques for Photovoltaic solar cells. Typically, the quest for the wide space needed to deploy PV systems has driven scientists to design multifunctional nanostructured materials for semitransparent solar cells (STSCs) technologies that can fit in available household environmental and architectural spaces. Specifically, Plasma Enhanced Chemical Vapor Deposition (PECVD) technique demonstrated the ability to produce highly transparent coatings with the desired charge carrier mobility. The aim of the present article is to review the latest semi-transparent PV technologies that were impactful during the past decade with special emphasis on PECVD-related technologies. We finally draw some key recommendations for further technological improvements and sustainability.